2020
DOI: 10.1111/1747-0080.12635
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a peer review program using the validated DIET‐COMMS tool to assess dietitians' communication skills in the workplace

Abstract: AimsCommunication is the main method used by dietitians to conduct their practice. Yet, few evidence‐based tools are available to assess dietitians' communication skills to guide skill development. Further, workplace peer review programs for assessment of communication skills are not standard practice. DIET‐COMMS is a validated tool to assess dietitians' communication skills in patient consultations. The aims of this study were to implement a workplace peer review program using the DIET‐COMMS tool, assess diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…A training package to support the use of the tool was developed with most of the 15 respondents in a preliminary evaluation finding it useful 63 . The tool was used in an Australian study describing the successful implementation of a workplace peer review of communication skills programme 59 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A training package to support the use of the tool was developed with most of the 15 respondents in a preliminary evaluation finding it useful 63 . The tool was used in an Australian study describing the successful implementation of a workplace peer review of communication skills programme 59 …”
Section: Resultsmentioning
confidence: 99%
“…63 The tool was used in an Australian study describing the successful implementation of a workplace peer review of communication skills programme. 59 Recognising the increased use of both telehealth and online education, a study exploring the views of 24 dietetic educators in Australia and New Zealand regarding assessing communication skills in a telehealth setting concluded that non-verbal communication skills were the most challenging to assess and produced recommendations on assessment in this setting for students and educators. 64 Assessment tools to date have been developed for use by students and educators, but a pilot study including six student dietitians in the USA reported that patient feedback delivered via a bespoke questionnaire was perceived by students to be authentic and valuable.…”
Section: Assessment Of Communication Skills In Dietetic Education And...mentioning
confidence: 99%
“…Still remaining, though, are practical questions regarding how this could be achieved, how effective it would be and what tools could be used to assess skill attainment. Specific validated tools such as DIET‐COMMS have been successfully utilised to support peer review in dietetics 54 . Nevertheless, training is required to support the effective use of any assessment tool and to ensure the correct use and provision of supportive feedback, a concern raised in this survey.…”
Section: Discussionmentioning
confidence: 99%
“…Specific validated tools such as DIET-COMMS have been successfully utilised to support peer review in dietetics. 54 Nevertheless, training is required to support the effective use of any assessment tool and to ensure the correct use and provision of supportive feedback, a concern raised in this survey. A literature review and synthesis of relevant guidance and regulations, across a range of healthcare professions, has found that the use of video-recording healthcare communication, as already happens routinely in medicine, is acceptable and worthwhile, although ethical issues need to be considered.…”
Section: Post-registrationmentioning
confidence: 99%